Antimicrobial action of NeoMTA Plus on mono- and dual-species biofilms of Enterococcus faecalis and Candida albicans: An in vitro study. (December 2020) - Jacob, Vanessa Peret; Paião, Luana Isabel; da Silva, Ana Carolina Gomes; Magario, Mychelle Keiko Watanabe; Kaneko, Taís Yukari; Martins, Christine Men; Monteiro, Douglas Roberto; Mori, Graziela Garrido
Highlights: The presence of microorganisms cannot be removed completely with conventional treatment. Microorganisms may be organized in microbial biofilms which is more difficult to eliminate. A significant number of new bioactive endodontic cements have been introduced to endodontics, such as NeoMTA Plus. NeoMTA Plus antimicrobial activity needs to be studied, especially against microbial biofilms. Abstract: Objective: To evaluate the antimicrobial action of NeoMTA Plus on mono- and dual-species biofilms of Enterococcus faecalis and Candida albicans . Material and methods: A total of 171 sterile dentin blocks, measuring 4 mm × 4 mm × 1 mm, were incubated in media containing E. faecalis (3.1 × 10 8 cells/mL) and/or C. albicans (1 × 10 7 cells/mL) for 2 d. These blocks were randomly divided into three groups: the control (no treatment with biomaterials), MTA (treated with an MTA sample with width and thickness same as those of the dentin block after the material was set), and NeoMTA Plus (treated with NeoMTA Plus in a fashion similar to the treatment of the MTA group) groups. The biomaterials remained in contact with the biofilms for 24 h. Quantitative analyses of the number of colony-forming units (CFUs) and metabolic activity (XTT), were performed. Furthermore, qualitative analysis of biofilm structure was performed by scanning electron microscopy. Data were statistically analyzed considering a significance level of 5%. Results: XTT and the number of CFUs were similar among the groups (p > 0.05). The type of biofilm (mono- or dual-species) or the biomaterial used (MTA or NeoMTA Plus) did not affect the results. Biofilm structure exhibited a robust architecture composed of yeast and bacterial cell multilayers and was homogeneous among the groups. Conclusion: NeoMTA Plus was not effective against mono- and dual-species biofilms of E. faecalis and C. albicans . Further research investigating biofilm removal methods including those involving the use of biomaterials with antiseptics and other supporting therapies is warranted.